2020
DOI: 10.1590/pboci.2020.073
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Antibacterial Effect of Photodynamic Therapy with Methylene Blue

Abstract: How to cite this article: Catão MHCV, Batista ALA. In vitro evaluation of the antibacterial effect of photodynamic therapy with methylene blue. Pesqui Bras Odontopediatria Clín Integr. 2020; 20:e4980.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Because of the role of biofilm formations in the successful establishment of infection, its destruction is an important way of curbing gram-positive bacterial infections. PDT has been shown to reduce the formation of biofilm in various studies [ 26 ]. We have also shown that PDT reduces the formation of biofilms following the use of Hypocrellin B and light [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the role of biofilm formations in the successful establishment of infection, its destruction is an important way of curbing gram-positive bacterial infections. PDT has been shown to reduce the formation of biofilm in various studies [ 26 ]. We have also shown that PDT reduces the formation of biofilms following the use of Hypocrellin B and light [ 27 ].…”
Section: Discussionmentioning
confidence: 99%